Enhancing Information Technology On Organizational Performance Through In Cement Industry South Sulawesi - Muhammad Kafrawi Yunus; Haris Maupa; Irawati HM; Muhammad Akhsan Tenrisau (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
This study aims to analyze and test the effect of information technology on organizational performance in the cement industry in South Sulawesi, namely PT Semen Tonasa and PT. Bosowa Cement. This research was conducted quantitatively using a questionnaire as a data collection tool. The structural equation model is used to test the hypothesis using the Smart-PLS Version 3.0 program. Data was collected by administering questionnaires to 94 employees of the two cement companies. The results of this study indicate that information technology has a direct and significant effect on organizational commitment. Information technology has no direct significant impact on employee motivation. Information technology, organizational alerts, and employee motivation have a direct positive impact on organizational performance. Information technology positively and significantly indirectly affects organizational performance through organizational commitment and employee motivation.